Development and evaluation of a portable raw material mixing system for food extrusion - Kruger, Dirk Jacobus (My University, 2014)
In this study, mixing is identified to be the most crucial step during the pre-processing process of extruded food and feed stocks. This study therefore aimed to investigate different mixing techniques in an effort to identify the most effective method and its feasibility to pilot plant application for food extrusion processing. The study furthermore considered the methods of mixing with the view to incorporating the identified method in a standard portable cargo container. The research included an investigation and the design of an inexpensive pre-processing control system that would also save space in such applications where storing facilities for ingredients are housed. After investigating different mixing solutions, a V-blender was identified to be a feasible option. It is suggested that by adding a third leg to the V-blender, to obtain what is dubbed as a "Y"-blender, the effectiveness of mixing would be improved upon - not only in the specified application but with respect to mixing in general. In order to evaluate and compare the effectiveness of the mixers, rapid prototyping models of a V- and a Y- blender, with capacities of about 7.6 litres each, were produced from medium density fibre-board (MDF) with the aid of a laser cutter. It was found that, for a recipe consisting of 87% fine yellow maize, 12.75% fine sugar and 0.25% colorant, the effectiveness of mixing within the V-blender was greatly influenced by the level to which it was filled. This was not the case for the Y-blender. This therefore suggested that a Y-blender is the ideal solution for the given application. A layout of a pre-processing system that fits in a standard shipping container and can accommodate six funnel-shaped raw material storage bins with a feed conveyor leading to a Y-blender is designed and a rapid prototyping model of the most vital components of the system is produced. A novel control system using the IOIO USB controller coupled to an Andriod device is developed and this sub-system, with dedicated software, is coupled to the prototyped pre-processing set-up and operated successfully.
MIng (Mechanical Engineering), North-West University, Potchefstroom Campus, 2014
Keywords: Raw material; Mixing; Extrusion; Food extrusion; Extrudate